2016
DOI: 10.3402/rlt.v24.29920
|View full text |Cite
|
Sign up to set email alerts
|

University students and faculty have positive perceptions of open/alternative resources and their utilization in a textbook replacement initiative

Abstract: This is contribution no. 16-114-J from the Kansas Agricultural Experiment Station.The Kansas State University Open/Alternative Textbook Initiative provides grants to faculty members to replace textbooks with open/alternative educational resources (OAERs) that are available at no cost to students. Open educational resources are available for anyone to access, while alternative educational resources are not open. The objective of this study was to determine the perceptions towards OAERs and the initiative, of st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
36
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 9 publications
5
36
0
3
Order By: Relevance
“…Sixty-four percent of faculty members reported that using OER facilitated meeting diverse learners' needs and sixtyeight percent perceived greater student satisfaction with the learning experience when using OER. Delimont et al (2016) surveyed 524 learners and thirteen faculty members across thirteen courses at Kansas State University regarding their experiences with both "open" and "alternative" resources (where alternative resources refer to free, but copyrighted materials). When students evaluated the statement, "I prefer using the open/alternative educational resource instead of buying a textbook for this course (1 = Strongly disagree, 7 = Strongly agree)" they rated it 5.7 (moderately agree).…”
Section: Studies Examining Direct Comparisons Between Oer and Ctmentioning
confidence: 99%
“…Sixty-four percent of faculty members reported that using OER facilitated meeting diverse learners' needs and sixtyeight percent perceived greater student satisfaction with the learning experience when using OER. Delimont et al (2016) surveyed 524 learners and thirteen faculty members across thirteen courses at Kansas State University regarding their experiences with both "open" and "alternative" resources (where alternative resources refer to free, but copyrighted materials). When students evaluated the statement, "I prefer using the open/alternative educational resource instead of buying a textbook for this course (1 = Strongly disagree, 7 = Strongly agree)" they rated it 5.7 (moderately agree).…”
Section: Studies Examining Direct Comparisons Between Oer and Ctmentioning
confidence: 99%
“…In a survey of 127 post-secondary educators, Pitt (2015) reports that 25% said using an open textbook had "enabled innovation or changed their pedagogical approach" (p. 146), but only a few explained in open-ended questions that they had revised an open textbook. From interviews with faculty who have adopted, adapted, or created an open textbook or other OER, Delimont, Turtle, Bennett, Adhikari, & Lindshield (2016) report that 12 out of 13 faculty said they preferred to teach with OER rather than commercial textbooks, and out of those, 11 gave customizability of OER as a reason for their preference. Neither study, however, focuses on how faculty are revising OER, and overall there is little research in the extant literature on the degree to which faculty or students are revising OER, how they are doing so, and what impact this may have on student learning outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…A third of the sample supported these ratings with comments that touched on technical advantages (e.g., ability to easily search, change print size, and navigate the text), learning aids (e.g., embedded videos and quizzes), alignment of the text with lectures, cost savings, convenient access, and the quality of the writing. Finally, 524 students at Kansas State University using open or alternative textbooks rated the quality of these resources as above average (5.7 on a 7 point scale; Delimont, Turtle, Bennett, Adhikari, & Lindshield, 2016). …”
Section: Introductionmentioning
confidence: 99%